Pertimbangan Pasar Kerja Mahasiswa Akuntansi Pada Profesi Akuntan Publik - Ratih Anggraini Siregar; Feby Yoana Siregar (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2021)
This study aims to test the influence of job security, job availability and ease of access to job openings to career selection as a public accountant. The data used in this study is primary data received directly from research respondents, namely 200 students. To see how much influence job security, job availability and ease of access to job openings to career selection as a public accountant. The results of this study found there is a significant influence of job security, availability of employment and ease of access to job openings to career selection as a public accountant. As well as consideration of the job market can be a benchmark for students in choosing a career as a public accountant.